2004
DOI: 10.1007/s00253-004-1608-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of genes for energy catabolism and hydrolytic enzymes in the filamentous fungus Aspergillus oryzae using cDNA microarrays and expressed sequence tags

Abstract: Aspergillus oryzae is a fungus used extensively in the fermentation industry. We constructed cDNA microarrays comprising 2,070 highly expressed cDNAs selected from the approximately 6,000 non-redundant expressed sequence tags (ESTs) in the A. oryzae EST database (http://www.aist.go.jp/RIODB/ffdb/index.html). Using the cDNA microarrays, we analyzed the gene expression profiles of A. oryzae cells grown under the glucose-rich (AC) and glucose-depleted (AN) liquid culture conditions used during the construction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
8

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 32 publications
4
59
0
8
Order By: Relevance
“…It has been reported that yeast chromosomes are rearranged frequently under starved culture conditions and that (AþT)-rich sequences or transfer RNA often mediate such rearrangements 20 . Our EST analysis shows that the expression profile in solid-state cultivation is similar to that observed when a carbon source is omitted 21 . These reports suggest that the acquired foreign DNA has been rearranged in a short period of time by large-scale solid-state cultivation since A. oryzae was domesticated from an ancestor of A. flavus 22 .…”
Section: Superfamily (Mfs) Transporter Genes (Supplementarysupporting
confidence: 64%
“…It has been reported that yeast chromosomes are rearranged frequently under starved culture conditions and that (AþT)-rich sequences or transfer RNA often mediate such rearrangements 20 . Our EST analysis shows that the expression profile in solid-state cultivation is similar to that observed when a carbon source is omitted 21 . These reports suggest that the acquired foreign DNA has been rearranged in a short period of time by large-scale solid-state cultivation since A. oryzae was domesticated from an ancestor of A. flavus 22 .…”
Section: Superfamily (Mfs) Transporter Genes (Supplementarysupporting
confidence: 64%
“…While exgA expression showed significant differences in some of the culture conditions described above, expression of the histone H4 gene, which showed expression typical of a housekeeping gene as control, 28) remained constant in all the culture conditions used in this study (Fig. 4E).…”
Section: Analysis Of the Biological Function Of Exgamentioning
confidence: 64%
“…28,31) Limitation of nutrition in solid state culture leads to the production of more hydrolases than in nutrition-rich conditions. 28) Riou et al have reported that ExgA productivity was highest when A. oryzae was grown with a carbon source of water-insoluble flavonoids, quercetin and rutin.…”
Section: Discussionmentioning
confidence: 99%
“…The available genome sequence enables identification of genes and functionally important regions of the genome. It has directed the research focus towards the development of genome-wide analysis methods for exploiting that information 2,23,24) , also in relation to fungal product formation and protein secretion 6,35,41) .…”
Section: Fungi In Biotechnologymentioning
confidence: 99%